COMMUNITY EMPOWERMENT MODEL IN THE JANGKANG WATER RECLAMATION VILLAGE AREA, BANGKA REGENCY - Muhammad Trysal; Dadang H. Purnama; Vieronica V. Sununianti (SOSIOEDUKASI, 2026)
This research aims to solve problems regarding community empowerment by developing a community empowerment model that is in accordance with the needs of the community in the Jangkang Water Reclamation Village Area. The background of the research began with the presence of the Jangkang Water Reclamation Village which is a reclamation in another form in the Riding Panjang Village Area managed by a subsidiary company of PT. Timah Tbk as the owner of the IUP, namely PT. Timah Agro Manunggal (PT. TAM), according to the rules that companies that have IUP are obliged to empower the surrounding community, but the community around the reclamation village has not been optimally affected by the Community Development and Empowerment (PPM) activities of both PT. Timah Tbk and PT. TAM as the manager of the Reclamation Village. In this study, qualitative methods are used and the paradigm used in this study is constructivism with this research strategy in the form of a case study approach. Data collection through observation, in-depth interviews, Focus Group Discussions (FGD) and documentation. Data is analyzed using data condensation, data display and conclusion drawn. The results of the study show that the presence of reclamation villages has not had a significant impact on the lives of the people around the area, the majority of people do not have critical awareness to know their position as the subject of empowerment so that the community is not only a recipient of assistance and does not know about the company's obligations in empowering the community through the Community Development and Empowerment (PPM) program, the community should empowered by providing training to increase their capacity. The people of Riding Panjang Village as the subject of empowerment already have strong social capital in the form of social harmony and the strength of social networks between communities. However, challenges are still encountered in the implementation of empowerment in the form of regulations between PT. Timah Tbk with PT. TAM, the lack of optimal human resources in Riding Panjang Village and the lack of good cooperation and synergy between the village and the manager of the reclamation village.